2024
DOI: 10.1126/science.adk4432
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotically plausible chemoselective pantetheine synthesis in water

Jasper Fairchild,
Saidul Islam,
Jyoti Singh
et al.

Abstract: Coenzyme A (CoA) is essential to all life on Earth, and its functional subunit, pantetheine, is important in many origin-of-life scenarios, but how pantetheine emerged on the early Earth remains a mystery. Earlier attempts to selectively synthesize pantetheine failed, leading to suggestions that “simpler” thiols must have preceded pantetheine at the origin of life. In this work, we report high-yielding and selective prebiotic syntheses of pantetheine in water. Chemoselective multicomponent aldol, iminolactone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…However, despite these advances, the spontaneous synthesis of peptides remains an elusive goal with direct ligation of α-aminonitriles yielding amino-imidazoles that block peptide synthesis (Figure 1A). 20 We recently demonstrated a chemoselective prebiotic synthesis of pantetheine (Figure 1C), 20 the functional fragment of the universal cofactor, coenzyme A, which is essential throughout all domains of life as an acyl-carrier. 13,14 The deep-seated role of pantetheine in biochemistry, for example in the Krebs cycle, fatty acid, and polyketide syntheses, has suggested that thiols may have played a key role in prebiotic chemistry, the "Thioester World" model for the origins of life.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, despite these advances, the spontaneous synthesis of peptides remains an elusive goal with direct ligation of α-aminonitriles yielding amino-imidazoles that block peptide synthesis (Figure 1A). 20 We recently demonstrated a chemoselective prebiotic synthesis of pantetheine (Figure 1C), 20 the functional fragment of the universal cofactor, coenzyme A, which is essential throughout all domains of life as an acyl-carrier. 13,14 The deep-seated role of pantetheine in biochemistry, for example in the Krebs cycle, fatty acid, and polyketide syntheses, has suggested that thiols may have played a key role in prebiotic chemistry, the "Thioester World" model for the origins of life.…”
mentioning
confidence: 99%
“… Coupling these nitriles, through transformation into thioacids 3 or thioimidates 4 (Figure B), allows efficient protecting-group-free peptide synthesis in water. However, despite these advances, the spontaneous synthesis of peptides remains an elusive goal with direct ligation of α-aminonitriles yielding amino-imidazoles that block peptide synthesis (Figure A) …”
mentioning
confidence: 99%
See 3 more Smart Citations